Histone acetyltransferases: Rising ancient counterparts to protein kinases1. Issue 2 (22nd November 2012) - Yuan, Hua; Marmorstein, Ronen; Trievel, Ray
Abstract Protein kinases catalyze phosphorylation, a posttranslational modification widely utilized in cell signaling. Histone acetyltransferases (HATs) catalyze a counterpart posttranslational modification of acetylation which marks histones for epigenetic signaling but in some cases modifies non‐histone proteins to mediate other cellular activities. In addition, recent proteomic studies have revealed that thousands of proteins are acetylated throughout the cell to regulate diverse biological processes, thus placing acetyltransferases on the same playing field as kinases. Emerging biochemical and structural data further supports mechanistic and biological links between the two enzyme families. In this article, we will review what is known to date about the structure, catalysis and mode of regulation of HAT enzymes and draw analogies, where relevant, to protein kinases. This comparison reveals that HATs may be rising ancient counterparts to protein kinases. © 2012 Wiley Periodicals, Inc. Biopolymers 99: 98–111, 2013.